2008
DOI: 10.1007/s00122-008-0710-x
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of iron deficiency chlorosis loci in soybean (Glycine max L. Merr.) advanced breeding lines

Abstract: Association mapping is an alternative to mapping in a biparental population. A key to successful association mapping is to avoid spurious associations by controlling for population structure. Confirming the marker/trait association in an independent population is necessary for the implementation of the marker in other genetic studies. Two independent soybean populations consisting of advanced breeding lines representing the diversity within maturity groups 00, 0, and I were screened in multi-site, replicated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 36 publications
1
76
0
7
Order By: Relevance
“…Merr.) two markers, Satt114 and Satt239, were found to be associated with iron deficiency chlorosis loci using advance breeding lines (Wang et al, 2008). In rice (Oryza sativa L.), microsatellite markers associated with yield and its components were identified in a variety trial, and many of them were located in regions where QTL had previously been identified (Agrama et al, 2007).…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Merr.) two markers, Satt114 and Satt239, were found to be associated with iron deficiency chlorosis loci using advance breeding lines (Wang et al, 2008). In rice (Oryza sativa L.), microsatellite markers associated with yield and its components were identified in a variety trial, and many of them were located in regions where QTL had previously been identified (Agrama et al, 2007).…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…A Mixed Linear Model (MLM) approach has been developed to account for multiple levels of relatedness simultaneously as determined by kinship estimates based on a set of random genetic markers . This model has been proven useful in genome-wide association studies to control the biases that may be caused by population structure and relatedness in other species e.g., maize (Zea mays L.) , rice (Wang et al, 2008). Another issue for association mapping is reliability, an issue of particular concern when the goal is to discover marker/trait associations that have broad application.…”
Section: Summary and Future Prospectsmentioning
confidence: 99%
“…Many alkaline soils also have high bicarbonate concentration (Mengel 1994;Rogovska et al 2007), which can inhibit Fe uptake Mengel 1994). Leaf chlorosis is a classical Fe deficiency sign, and negatively impacts yield in certain crops, such as soybean in the upper Midwest USA (O'Rourke et al 2007;Wang et al 2008). Under low Fe availability conditions, plants increase Fe uptake gene expression and protein activity (Morrissey and Guerinot 2009), which in dicot species includes ferric reductases (Jeong and Connolly 2009), iron transporters (Vert et al 2002), and H + -ATPases (Santi and Schmidt 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To identify more general molecular markers for MAS, association mapping in a natural population was developed for screening molecular markers, which are related to desired traits of crops. QTL for important traits in soybean have been identified by AM using SSR markers, including those related to protein content and iron deficiency (e.g., Wang et al, 2008;Jun et al, 2008). Importantly, however, AM cannot resolve problems of small-effect genes and multi-gene interaction, which has limited the application of AM in soybean.…”
Section: Application Of Gs In Soybean Genetic Breedingmentioning
confidence: 99%